Unveiling Trends in Online Learning Impact via Zoom and Google Meet: Mengungkap Tren Dampak Pembelajaran Online melalui Zoom dan Google Meet - Amar, Muhammad; Junaidi, Achmad; Lesmana, Dimas Bayu Putra; Abadi , Totok Wahyu (Universitas Muhammadiyah Sidoarjo, 2024)
This study employs bibliometric analysis to explore the impact of Google Meet and Zoom on students' comprehension of online learning during 2020-2021. Utilizing data from Crossref indexed articles and tools like Publish or Perish and VOSViewer, the research identifies dense thematic clusters and trends in scholarly literature. Results show significant publication activity, with dark blue indicating articles from 2020 and yellow from 2021, reflecting evolving research interests. This analysis enhances understanding of how virtual platforms influence educational practices, offering insights for educators and policymakers aiming to optimize online learning experiences. Highlights: Identifies dense thematic clusters in online learning research. Highlights significant publication trends using bibliometric analysis tools. Informs educators on optimizing virtual learning environments for student engagement. Keywords: Online learning, Google Meet, Zoom, Bibliometric analysis, Educational technology